DEVELOPMENT OF LEARNING MEDIA BASED ON LEARNING MANAGEMENT SYSTEM (LMS) TO IMPROVE STUDENT ENGAGEMENT AT STATE SENIOR HIGH SCHOOL 1 KETAPANG SAMPANG - Tri Puspawati, Septi Kartika; Hartati, Sulis Janu; Tobing, Victor Maruli Tua L (Jurnal Konseling Pendidikan Islam, 2025)
This study aims to develop an LMS-based learning media specifically designed to improve the engagement of students at SMA Negeri 1 Ketapang through an approach that integrates cognitive, affective, and behavioral aspects in digital learning. Using a Research and Development approach with the ADDIE model, the study involved 180 students in grades X and XI who were selected through purposive sampling. Research instruments included the Student Engagement Scale (reliability α = 0.89), the Technology Acceptance Model (reliability α = 0.85), and a learning outcome test (validity CVR = 0.78), with data analysis using descriptive and inferential statistics. The results showed a significant increase in student engagement: cognitive 34%, affective 41%, and behavioral 38% (p < 0.001). Correlation analysis revealed a strong relationship between student engagement and learning outcomes (R² = 0.72), with the gain score of the experimental group reaching 13.3 points versus 3.3 points for the control group. The system usage rate reached 89% of students with minimal access of 5 days per week, demonstrating the effectiveness of the developed LMS in transforming digital learning into a more interactive and meaningful experience.